2022
DOI: 10.3390/ijms23147761
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dysregulated miRNAs in the Pathogenesis, Diagnosis and Treatment of Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is an eye disease causing damage to the macular region of the retina where most of the photoreceptors responsible for central visual acuity are located. MicroRNAs (miRNAs) are small single-stranded non-coding RNA molecules that negatively regulate genes by silent post-transcriptional gene expressions. Previous studies have shown that changes in specific miRNAs are involved in the pathogenesis of eye diseases, including AMD. Altered expressions of miRNAs are related to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Studies revealed that circulating miRNAs could also serve as potential biomarkers for AMD detection (Urbańska et al, 2022;Elshelmani and Rani, 2023), as reported in other chronic diseases, such as cancer (El-Daly et al, 2023), osteoporosis (Messner et al, 2022), epilepsy (Xie et al, 2023), pulmonary hypertension (Düzgün et al, 2023), nephropathies (Sun et al, 2022), and hepatitis (Jiang et al, 2023). Furthermore, the significance of circulating miRNAs in numerous therapeutic areas makes them a promising asset for translational medicine applications (Pozniak et al, 2022).…”
Section: Macular Degenerationmentioning
confidence: 93%
“…Studies revealed that circulating miRNAs could also serve as potential biomarkers for AMD detection (Urbańska et al, 2022;Elshelmani and Rani, 2023), as reported in other chronic diseases, such as cancer (El-Daly et al, 2023), osteoporosis (Messner et al, 2022), epilepsy (Xie et al, 2023), pulmonary hypertension (Düzgün et al, 2023), nephropathies (Sun et al, 2022), and hepatitis (Jiang et al, 2023). Furthermore, the significance of circulating miRNAs in numerous therapeutic areas makes them a promising asset for translational medicine applications (Pozniak et al, 2022).…”
Section: Macular Degenerationmentioning
confidence: 93%
“…Treatment targets for AMD are thought to include several miRNAs implicated in either retinal pigment epithelium atrophy or choroidal neovascularization ( Urbańska et al, 2022 ). For neovascular AMD, anti-vascular endothelial growth factor therapy is a crucial treatment ( Cornel et al, 2015 ).…”
Section: Mirnas and Age-related Diseasesmentioning
confidence: 99%
“…The miR-15/107 group, the miR-17∼92 cluster, miR-21, miR-132, miR-296, miR-378, and miR-519c are some of these miRNAs. It is thought that miR-23a mimics reduce macular related-apoptosis whereas miR-23a inhibition increases it ( Ren et al, 2017 ; Urbańska et al, 2022 ).…”
Section: Mirnas and Age-related Diseasesmentioning
confidence: 99%
“…Their disruption or malfunction leads to many general disorders (cancer, inflammation, diabetes, cardiovascular, and neurologic diseases) [153,154]. Altered expressions (dysregulations) of different miRNAs are involved in AMD etiopathogenesis [155][156][157]. Circulating miRNAs may be potential diagnostic biomarkers for AMD [158,159].…”
Section: Antioxidative Role Of Circulating Micrornasmentioning
confidence: 99%
“…According to another study, miRNA-23, miRNA-27a, miRNA-34, miRNA-126, miRNA-146a, and miRNA-155 are the most frequently dysregulated miRNAs in AMD. All of them are associated with oxidative stress, apoptosis, inflammation, and angiogenesis; however, in oxidative stress, miRNA-27a and miRNA-146a are mainly involved; miRNA-27a affects RPE by prooxidants, and miRNA-146a is up-regulated by ROS [155].…”
Section: Antioxidative Role Of Circulating Micrornasmentioning
confidence: 99%